A correlação da tabela do imposto de renda retido na fonte : consequências sobre a economia brasileira e seus setores - Leite Junior, Mauro Antônio de Figueiredo (2023)
This dissertation aims to evaluate the impact of changes in the tax burden, personal income tax (IRPF), on the consumption of Brazilian families. Using data from the family budget survey (POF), Brazilian families were divided into five (5) income ranges, the surplus that could be consumed between adjacent ranges was evaluated, if the ranges were corrected, and the impact was estimated via shocks, through general equilibrium, in household consumption on an aggregate basis. To carry out the estimates, methodological techniques of computable general equilibrium were used. It is known that Brazil has a very complex tax structure, which impacts not only household consumption but also the country's productive structure. In this sense, the dissertation, in addition to presenting the effects of shocks on consumption, also simulated the impact of such shocks from a macroeconomic and sectoral point of view. Even when factoring in government spending tax offsets, the economy could grow by about 1.5% in the short term and 2.1% in the long term. If the public sector were capable of absorbing indebtedness and there was no compensation, that is, cutting expenses, the economy could grow even 3% in the long term.